Comparison of the effect of individual and couple emotion focoused therapy on coping with postmenstrual changes in women with premenstrual disorder - Javadi, Neda; Kooshki, Shirin; Golshani, Fatemeh; Baghdasarians, Anita (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study aims to determine the effect of individual and couple emotional therapy on coping Method: The research design was quasi-experimental pre-test and post-test with three experimental groups and control group. The statistical population of the study consisted of all married women in Tehran. From this population, 53 people were selected as a statistical sample by the available method and were randomly replaced in three groups (two experimental groups and one control group). The required findings were collected using a questionnaire on coping with premenstrual changes (Reid et al., 2014) in three rounds: pre-test, post-test and follow-up test, and using size analysis of variance test. ¬Repeated capture was analyzed. Results: Findings showed that individual emotion-oriented therapies and couple-emotion-oriented therapies in the experimental groups in the post-test stages compared to the control group increased coping strategies with premenstrual changes and this increase was stable over time. Conclusion: There is a significant difference between the effectiveness of individual emotion-oriented therapies and emotion-oriented couple therapy on the components of coping strategies. "Self-care" and "avoidance of harm" have been more effective than couple therapy.